2022
DOI: 10.3390/polym14204253
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exopolysaccharides of Pseudomonas in Heavy Metal Removal and Other Remediation Strategies

Abstract: Pseudomonas biofilms have been studied intensively for several decades and research outcomes have been successfully implemented in various medical and agricultural applications. Research on biofilm synthesis and composition has also overlapped with the objectives of environmental sciences, since biofilm components show exceptional physicochemical properties applicable to remediation techniques. Especially, exopolysaccharides (ExPs) have been at the center of scientific interest, indicating their potential in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…It has been shown that Pseudomonas can reduce highly toxic pentavalent V to less toxic tetravalent V under certain conditions, thereby reducing its toxicity [67]. At the same time, some studies have shown that Pseudomonas has a certain resistance to heavy metals and is widely used in heavy metal remediation [68][69][70][71]. Additionally, Actinobacteria and Firmicutes were dominant among the root endophytes in these samples, which could be attributed to their high tolerance to heavy metals.…”
Section: Microbial Community Responsesmentioning
confidence: 88%
“…It has been shown that Pseudomonas can reduce highly toxic pentavalent V to less toxic tetravalent V under certain conditions, thereby reducing its toxicity [67]. At the same time, some studies have shown that Pseudomonas has a certain resistance to heavy metals and is widely used in heavy metal remediation [68][69][70][71]. Additionally, Actinobacteria and Firmicutes were dominant among the root endophytes in these samples, which could be attributed to their high tolerance to heavy metals.…”
Section: Microbial Community Responsesmentioning
confidence: 88%
“…On the yeast front, the presence of exopolysaccharides (EPS) may influence the soil-root interface, thereby reducing the availability of Cu. The intricate role of microbial EPS production in enhancing soil aggregation, particularly under challenging conditions such as salinity and drought, has been well documented [59][60][61]. Recent studies have further underscored the significant biotechnological potential of EPS, highlighting its efficacy in both the sequestration and remediation of heavy metals [50,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…• Phytohormonal plant growth stimulation, N 2fixation and improved nutrient acquisition (Singh et al, 2023) • Solubilization of P and other sparingly soluble nutrients (Barin et al, 2022) • Promotion of mycorrhization (Viollet et al, 2017) and legume nodulation (Soussou et al, 2017) • Soil aggregation (Sandhya and Ali 2015) and metal detoxification (Balıḱováet al, 2022) by release of exopolysaccharides…”
Section: Type Of Pgpmsmentioning
confidence: 99%